Use of esketamine for tracheoscopic drug injection: a randomized controlled trial - Zhao, Xiaoming; Zhou, Zhendong; Li, Zhenhua; Hu, Zhaolan; Yu, Yuanyuan (Frontiers in Medicine, 2024)
Background: Sufentanil may induce hypotensive bradycardia and other adverse reactions in elderly patients during anesthesia, while esketamine exhibits sedative and analgesic effects with minimal impact on respiration and circulation. The objective of this study was to investigate the impact of these two anesthetics on vital signs in patients undergoing bronchoscopy and lavage under general anesthesia. Method：This study was a randomized controlled trial with a parallel design. A total of 100 patients aged ≥60 years with ASAI or II who were undergoing bronchoscopy and lavage were randomly assigned to two groups: group A (esketamine, n=50) and group B (sufentanil, n=50). During anesthesia induction, both groups received intravenous infusion of propofol at a dose of 1.5ml/kg and atracurium. In group A, esketamine at a dose of 0.3mg/kg was injected; in group B, sufentanil at a dose of 0.2μg/kg was injected intravenously. Subsequently, a laryngeal mask was inserted and connected to an anesthesia machine for mechanical ventilation. Anesthesia maintenance involved continuous intravenous infusion of propofol at a dose of 3ml/kg. The mean arterial pressure (MAP), heart rate (HR), and blood oxygen saturation (SpO2) were recorded at various time points: before anesthesia injection (T0), after laryngeal mask insertion (T1), 5 minutes after the operation started (T2), 15 minutes after the operation started (T3), and before the end of the operation(T4). Additionally, the recovery time was recorded. Results: The blood pressure of patients in the esketamine group exhibited higher levels compared to those in the sufentanil group at multiple time points during the operation, while maintaining a more stable intraoperative blood pressure and shorter postoperative recovery time than that observed in the sufentanil group. The blood pressure and heart rate of patients in the esketamine group exhibited significant fluctuations after laryngeal mask implantation compared to pre-anesthesia induction, with a statistically significant increase observed. Conversely, no significant changes were observed in the sufentanil group. The heart rate and oxygen saturation showed no significant differences between the two groups, nor did the amount of propofol administered during the procedure.